Non-remunerated work in Colombia (2014)
This document constitutes progress in analyzing the visibility of the care economy (non-remunerated work) in Colombia, based on some general reflections on the sexual division of labor, welfare and the care economy. Thus the value of statistics on the use of time stands out not only for issues related to gender, but also in terms of equality, exclusion and poverty. By analyzing the available information we can find that care services are highly concentrated in women which easily leads to the conclusion that this work is producing the goods with major determinant for the development of future generations social externality and produces widespread benefits who do not pay for them, hence the importance of visibility.